Metabolic syndrome and risk of coronary artery disease in west of Iran - Berenjy, Shila; Rahmat, Asmah; Yassin, Zaitun; Lye, Munn Sann; Sahebjamee, Farzad; Hanachi, Parichehr (Marsland Press, 2012)
A major concern about MS (Metabolic Syndrome) and CAD (Coronary Artery Disease) is that patients with these defects are at higher risks of mortality and morbidity due to a combination of MS risk factors. The purpose of study was to examine the differences between CAD and non-CAD patients regarding their MS components and selected lifestyle behaviors (i.e., dietary intake, physical activity patterns, and smoking habits) and there was an attempt to determine whether MS was an independent risk factor for CAD among the patients. The study used case-control methodology for collection and analysis of the data. 600 participants recruited for study. CLR was applied to quantify the odds Ratio (OR) of CAD associated with MS and its components and other life style risk factors of CAD. MS increased the risk of CAD 4.19 times significantly (OR=4.19, 95%CI=2.603-6.47, P= 0.0001). Multivariate analysis showed that MS conveyed no additional predictive information beyond its components (odds Ratio=0.81, p=0.6). The focus of physicians should be treatment of individual CAD risk factors, using the metabolic syndrome will not improve prediction of CAD as compared with detailed information on individual CAD risk factors.